2017
DOI: 10.1038/s41598-017-02293-z
|View full text |Cite
|
Sign up to set email alerts
|

Treatment effects of the traditional Chinese medicine Shenks in bleomycin-induced lung fibrosis through regulation of TGF-beta/Smad3 signaling and oxidative stress

Abstract: Pulmonary fibrosis is a kind of devastating interstitial lung disease due to the limited therapeutic strategies. Traditional Chinese medicine (TCM) practices have put forth Shenks as a promising treatment approach. Here, we performed in vivo study and in vitro study to delineate the anti-fibrotic mechanisms behind Shenks treatment for pulmonary fibrosis. We found that regardless of the prophylactic or therapeutic treatment, Shenks was able to attenuate BLM-induced-fibrosis in mice, down regulate extracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Polysaccharide (ESP-B4) from Ephedra sinica Stapf against airway and pulmonary inflammation revealed that ESP-B4 could downregulate the production of TGF-β1, p-Smad2 and p-Smad3, upregulate the expression of Smad7, which indicated that ESP-B4 reduced airway and pulmonary inflammation by regulating the TGF-β1/Smad2 pathway [118]. Shen-mai-kai-fei-san (Shenks) has been shown to be effective in the treatment of pulmonary fibrosis [119]. In vivo and in vitro studies demonstrated that Shenks inhibited fibrosis by blocking TGF-β pathway.…”
Section: Targeting Tgf-β1/smad Signaling By Extracts and Compound Prementioning
confidence: 99%
“…Polysaccharide (ESP-B4) from Ephedra sinica Stapf against airway and pulmonary inflammation revealed that ESP-B4 could downregulate the production of TGF-β1, p-Smad2 and p-Smad3, upregulate the expression of Smad7, which indicated that ESP-B4 reduced airway and pulmonary inflammation by regulating the TGF-β1/Smad2 pathway [118]. Shen-mai-kai-fei-san (Shenks) has been shown to be effective in the treatment of pulmonary fibrosis [119]. In vivo and in vitro studies demonstrated that Shenks inhibited fibrosis by blocking TGF-β pathway.…”
Section: Targeting Tgf-β1/smad Signaling By Extracts and Compound Prementioning
confidence: 99%
“…The pathology of IPF is characterized by migration, proliferation and differentiation of fibroblast and remodeling of the extracellular matrix (ECM) 3 . Fibroblasts have been noted to play a central role in the fibrotic processes regulated by transforming growth factor-β (TGF-β) 4 , 5 or other profibrotic mediators, such as platelet-derived growth factor (PDGF) 6 , 7 and connective tissue growth factor (CTGF) 8 . These fibroblasts characterized by abnormal α-SMA and fibrillar collagens expression are called myofibroblasts 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence suggests that excessive ROS may directly interact with cellular biomolecules, such as lipids, proteins and nucleic acids, and cause damage to cellular constituents [45]. Within cells, there exists an antioxidant system capable of scavenging ROS, which comprises enzymatic antioxidants such as catalase, superoxide dismutase (SOD), guaiacol peroxidase (GPX), as well as non-enzymatic scavengers including GSH, vitamin C and vitamin E [46]. Studies have revealed that GSH is a predominant antioxidant that scavenges cellular ROS and other reactive nitrogen species through non-enzymatically reacts with radicals in a direct manner or indirectly enzymatic reaction [47,48].…”
Section: Discussionmentioning
confidence: 99%